VGLUT2/Cdk5/p25 Signaling Pathway Contributed to Inflammatory Pain by Complete Freund’s Adjuvant - Yuwen Tang; Zhiyou Peng; Shoujun Tao; Jianliang Sun; Wenyuan Wang; Xuejiao Guo; Gonglu Liu; Xianzhe Luo; Yuan Chen; Yue Shen; Haixiang Ma; Peng Xu; et al. (Pain Research and Management)
Vesicular glutamate transporter type 2 (VGLUT2) is known to play an important role in mediating heat hyperalgesia induced by inflammation. However, the underlying mechanism for this activity is poorly understood. Cyclin-dependent kinase 5 (Cdk5), serving as a key regulator in modulating release of glutamate, acted a key player in the formation of heat hyperalgesia of inflammatory pain. However, it remains unknown whether there is a bridge between Cdk5 and VGLUT2 for mediating inflammatory pain. Therefore, we designed the experiment to determine whether VGLUT2 signaling pathway is involved in inflammatory pain mediated by Cdk5 in the inflammatory pain model induced by complete Freund’s adjuvant (CFA). Our results showed that the coexpression of Cdk5/VGLUT2 in small- and medium-sized neuronal cells of the dorsal root ganglion (DRG) and spinal cord between days 1 and 3 following subcutaneous injection of CFA was significantly increased. Moreover, our study revealed that the expression of VGLUT2 protein in the DRG and spinal cord was remarkably increased between days 1 and 3 following CFA injection and was significantly reduced by roscovitine, a selective antagonist of Cdk5. Additionally, p25 but not p35, an activator of Cdk5, protein was significantly increased by CFA and reduced by roscovitine. Our findings suggested that VGLUT2/Cdk5 signaling pathway contributes to inflammatory pain mediated by Cdk5/p25.